Environmental advantages of the reverse logistics: a case study in the batteries collection in Brazil - Geraldo Cardoso de Oliveira Neto; Mauro Silva Ruiz; Auro Jesus Cardoso Correia; Henrique Manoel Riane Mendes (Production)
Abstract Paper aims Evaluate the environmental advantages of the Reverse Logistics of Portable Batteries carried out by the Brazilian Electrical and Electronics Industry Association (ABINEE). Originality The adoption of reverse logistics of batteries contributed with the minimization of environmental impact and stimulated the manufacturers of electronics in the adhesion of sector agreement as well as strengthened the players of reverse chain. Research method A case study was developed by means of interviews and documental analysis, and for data analysis, the mass balance was carried. Main findings 4,304,465 batteries were collected, representing 176,422kg of both solid and chemical wastes, which were disposed properly, reducing the environmental impact. Implications for theory and practice The theoretical contribution consists in environmental assessment by means of mass balance of the adoption of reverse logistics of batteries, and the practical contribution consists in stimulating the electronic manufacturers to develop social license among the community, government and players of reverse chain.